2016
DOI: 10.4155/fmc-2016-0083
|View full text |Cite
|
Sign up to set email alerts
|

Insect-Derived Short Proline-Rich and Murine Cathelicidin-Related Antimicrobial Peptides Act Synergistically on Gram-Negative Bacteria In Vitro

Abstract: CRAMP synergistically enhances the activity of proline-rich AMPs, which will allow evaluating their therapeutic potential more precisely in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…At the same time, ChMAP-28 did not restore the activity of mini-ChBac7.5Nα against P. aeruginosa , and no synergy was observed. These findings are consistent with the previous study that revealed the lack of synergy between Pro-rich AMPs and the membranolytic peptide CRAMP while testing antimicrobial activity against P. aeruginosa ( Knappe et al, 2016 ). Surprisingly, a pronounced synergistic effect was observed against S. aureus 209P with MICs of both peptides almost identical to those measured in a salt-free medium, thus resulting in FICI of 0.188.…”
Section: Resultssupporting
confidence: 93%
“…At the same time, ChMAP-28 did not restore the activity of mini-ChBac7.5Nα against P. aeruginosa , and no synergy was observed. These findings are consistent with the previous study that revealed the lack of synergy between Pro-rich AMPs and the membranolytic peptide CRAMP while testing antimicrobial activity against P. aeruginosa ( Knappe et al, 2016 ). Surprisingly, a pronounced synergistic effect was observed against S. aureus 209P with MICs of both peptides almost identical to those measured in a salt-free medium, thus resulting in FICI of 0.188.…”
Section: Resultssupporting
confidence: 93%
“…Several PrAMPs derived from artiodactyl or insect peptides act by interfering with bacterial protein synthesis [ 19 , 34 , 39 ]. To evaluate if the cePrAMPs also targeted this process, in vitro transcription/translation assays were carried out in their presence, assessing the inhibition of the synthesis of a reporter luciferase ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the plasma concentrations do not substantiate efficient treatment with either of the four PrAMPs when considering their in vitro antimicrobial activities determined with standard MIC-testing methods, which are most likely not the proper conditions to predict in vivo efficacies of PrAMPs. Synergistic effects with intrinsic antimicrobial substances produced by the host, e.g., AMPs like CRAMP, and immunomodulatory effects could also explain this discrepancy (Ostorhazi et al, 2013; Otvos and Ostorhazi, 2015; Knappe et al, 2016b). The latter effect was studied for Onc72, but no immunomodulatory effects were observed on unstimulated and lipopolysaccharide (LPS)-stimulated murine dendritic cells or murine macrophages (Fritsche et al, 2012).…”
Section: Discussionmentioning
confidence: 99%